The subtle knife - Pullman, Philip, 1946- (London : Scholastic, 2011)
Will has just killed a man. He's on the run. His escape will take him far beyond his own world, to the eerie disquiet of a deserted city, and to a girl, Lyra. Her fate is strangely linked to his own, and together they must find the most powerful weapon in all the worlds...
Film tie-in.
Originally published: 1997.
Keywords: Belacqua, Lyra (Fictitious character) -- Fiction; Parry, Will (Fictitious character) -- Fiction; Fantastic fiction; Children's stories